2018
DOI: 10.1016/j.celrep.2018.10.062
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Delivery of Synthetic Human DNA-Encoded Monoclonal Antibodies Protect against Ebolavirus Infection in a Mouse Model

Abstract: SUMMARY Synthetically engineered DNA-encoded monoclonal antibodies (DMAbs) are an in vivo platform for evaluation and delivery of human mAb to control against infectious disease. Here, we engineer DMAbs encoding potent anti-Zaire ebolavirus (EBOV) glycoprotein (GP) mAbs isolated from Ebola virus disease survivors. We demonstrate the development of a human IgG1 DMAb platform for in vivo EBOV-GP mAb delivery and evaluation in a mouse model. Using this approach, we show that DMAb-11 and DMAb-34 exhibit functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 53 publications
1
71
0
Order By: Relevance
“…4c ). To assess levels and durability of in vivo expression, mice were conditioned to reduce the T cell compartment using CD4 and CD8-depleting antibodies, this has been shown to permit the expression of a human mAb construct in mice in the absence of a host anti-drug antibody (ADA) response 25 . Administration of dMAb 2-12C pDNA to the tibialis anterior muscle was associated an increased durability of circulating levels of the mAb in the serum compared to rec 2-12C, administered intravenously ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4c ). To assess levels and durability of in vivo expression, mice were conditioned to reduce the T cell compartment using CD4 and CD8-depleting antibodies, this has been shown to permit the expression of a human mAb construct in mice in the absence of a host anti-drug antibody (ADA) response 25 . Administration of dMAb 2-12C pDNA to the tibialis anterior muscle was associated an increased durability of circulating levels of the mAb in the serum compared to rec 2-12C, administered intravenously ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The literature describes that pDNA-mAbs can exhibit peak serum concentrations after just 2 weeks and then can express at consistent levels for 2-3 months and decline thereafter as the plasmid is lost from cells and then cleared from the serum due to the natural half-life of immunoglobulin G (IgG) [36][37][38][39][40][41]. Long-term small animal studies show the total duration of pDNA-mAb expression to be at least 1 year [42,43]. However, in contrast to viral vectors, synthetic DNA requires an efficient delivery system.…”
Section: Synthetic Dnamentioning
confidence: 99%
“…Xu et al reported Synthetic DNA vaccines: prime time is approaching Gary and Weiner 25 [33 ]. This platform continues to advance and DMAbs targeting influenza A and B [34,35], dengue [36], Chikungunya [37 ], Zika [38 ], and Ebola [35,39] with of protection in animal models.…”
Section: Syndna Biologics In the Preclinical Settingmentioning
confidence: 99%